2015
DOI: 10.4238/2015.may.22.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on diabetic rat endothelial cells and retinal lesions

Abstract: ABSTRACT.We investigated the effect of atorvastatin on vascular endothelial growth inhibitor (VEGI) expression in rats with diabetic retinopathy. Wistar rats were divided into a blank group and diabetic model group, which was further randomly divided into treatment and control groups. Rats in the treatment group received 10 mg/kg atorvastatin daily, while rats in the blank and control groups received normal saline. Rats were randomly euthanized at 3 or 6 months. Immunohistochemical staining was used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, Nielsen et al reported that statin use before a patient develops diabetes was not associated with further progression of DR over 13 years, using a nation-wide healthrelated database in Denmark. 27 Simvastatin increased circulating endothelial progenitor cells and reduced the development and progression of DR in rats. Atorvastatin significantly reduced the oxidative stress level in a rat model involving hyperlipidaemia 26 and decreased expression of vascular endothelial growth factor in rats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Nielsen et al reported that statin use before a patient develops diabetes was not associated with further progression of DR over 13 years, using a nation-wide healthrelated database in Denmark. 27 Simvastatin increased circulating endothelial progenitor cells and reduced the development and progression of DR in rats. Atorvastatin significantly reduced the oxidative stress level in a rat model involving hyperlipidaemia 26 and decreased expression of vascular endothelial growth factor in rats.…”
Section: Discussionmentioning
confidence: 95%
“…Atorvastatin significantly reduced the oxidative stress level in a rat model involving hyperlipidaemia 26 and decreased expression of vascular endothelial growth factor in rats. 27 Simvastatin increased circulating endothelial progenitor cells and reduced the development and progression of DR in rats. 28 Patients who are using statins showed a lower concentration of angiopoietin-2, which is known to increase permeability and to have proangiogenic characteristics, in the vitreous obtained at the time of vitreous surgery.…”
Section: Discussionmentioning
confidence: 95%
“…11 However, potent statin has been shown to affect the mechanism of diabetic retinopathy in preclinical trials and also has a more profound effect than standard statin used in the aforementioned study. 1518 The threshold for statin therapy in today’s practice is currently lower compared to that a decade ago, and diabetic patients (40–75 years old) are recommended to take moderate-intensity statin at minimum. 19 A moderate-intensity statin regimen is defined as the dose of statin that is expected to reduce the low-density lipoprotein cholesterol (LDL-C) level by 30%–50% and a high-intensity statin regimen is defined as the dose of statin expected to reduce LDL-C by ⩾50%.…”
Section: Introductionmentioning
confidence: 99%
“…Through their immunomodulatory, antioxidant and anti‐inflammatory properties, statins can influence some of these mediators. For instance, it was shown that statins can reduce the expression of fractalkine , IL‐17 , IL‐13 receptor , IL‐5 and IL‐4 . In fact, preclinical studies have demonstrated that statins prevent the inflammatory bone reabsorption in experimental periodontitis .…”
mentioning
confidence: 99%